A novel CRYBB2 missense mutation causing congenital autosomal dominant cataract in an Italian family. - Faletra, Flavio; d'Adamo, Adamo Pio; Pensiero, Stefano; Athanasakis, Emmanouil; Catalano, Dario; Bruno, Irene; Gasparini, Paolo (Ophthalmic Genet, 2013)
Congenital cataract is a leading cause of visual impairment in children and brings approximately 10% of childhood blindness worldwide. Molecular analysis revealed ~60 loci to be associated with several phenotypes of childhood cataracts. Until now, more than 30 loci and 18 genes on different chromosomes have been associated with autosomal dominant congenital cataract (ADCC). Here, we present a three-generation Italian family with a non syndromic ADCC. A linkage analysis carried out using HumanCytoSNP-12 DNA Analysis BeadChip led us to identify ten genomic regions virtually involved in the disease. All the genes located in these regions were scored for possible relationship with ADCC and, according to a strict clinical and genetic selection, 4 genes have been analyzed. A novel sequence variant was found in the CRYBB2 gene (p.Ser143Phe). This variant affects a conserved aminoacid in the third Greek key motif of the protein, cosegregates with the disease phenotype in all affected individuals and is not present both in the unaffected family members and 100 healthy control subjects. Finally, we identified the first CRYBB2 mutation in an Italian family causing a clinical picture of ADCC.
Keywords: Amino Acid Sequence; beta-Crystallin B Chain; Cataract; DNA Mutational Analysis; Female; Genes, Dominant; Genetic Linkage; Genotype; Humans; Italy; Male; Molecular Sequence Data; Mutation, Missense; Pedigree; Phenotype